Pediatric respiratory assessment measure score in assessing the severity of acute asthma in children - Prasanna, R.; Moidu, Fayrouz; Pasupathy, Sekar (International Journal of Contemporary Pediatrics, 2019)
Background: Asthma is a chronic inflammatory disease of the lung airways resulting in episodic airflow obstruction. Management of acute pediatric asthma depends on assessment of asthma severity which is difficult in children due to poor coordination. This study is to evaluate the usefulness of a simple yet effective alternative like Pediatric respiratory assessment measure (PRAM) score in assessing the severity and outcome of an acute exacerbation of wheeze in children and to identify the PRAM score predicting the need for hospitalization. Methods: A prospective cohort study was done on 127 children for a period of 2 months in 2018, admitted with acute exacerbation of wheeze using PRAM scores at admission and following each treatment modalities. Usefulness of score in assessing severity was evaluated. Results: Increasing severity was associated with increasing initial PRAM score. Initial mean PRAM score of 11 in severe persistent forms, 7 in moderate persistent, 6.73 in mild persistent and 5.37 in mild intermittent was found. 59.1% of patients had a positive family history. The most common trigger factor according to our study was viral upper respiratory tract infection (50.4%) followed by exposure to dust (13.4%). Patients who were admitted to the Pediatric Intensive Care Unit (PICU) had the maximum number of interventions. Conclusions: In our study, statistically it was proved that PRAM Score is a tool that can be used across different ages and PRAM Score is a tool that can be used to assess severity of asthma.